Warriors, pacifists and empires: race and racism in international thought before 1914. (10th January 2022) - Ashworth, Lucian M
Abstract : This article charts racist ideas in early thought on international affairs. It specifically uncovers how debate between two theoretical camps—conservative/proto-realists and liberal/pacifists—created an illusion of critical enquiry, hiding the racist assumptions existing in both camps. Abstract: Before 1914 scholars of international thought frequently relied on racist arguments, yet the ways that race was used varied widely from author to author. This article charts the way that race was used by two groups of Anglophone writers. The warriors used biological arguments to construct views of international affairs that relied on racist analysis. Pacifists might have used racist language that relied more on cultural prejudices, and would often base their more progressive views of international affairs on the idea of a civilizing mission. Using A. T. Mahan and Brooks Adams as exemplars of the warrior approach, and Norman Angell and H. N. Brailsford for the pacifists, I argue that race and racism play an important part in international thought before the First World War. This racism was directed at the colonized in the global South, Indigenous peoples in settler colonial states, and Jews in the global North. This use of race and racism in pre-First World War international thought has implications for how we view the development of International Relations today. It is not just statues and stately homes that require a thorough reassessment of attitudes to race, but also our understanding of the progression of ideas in international thought.